Preliminary experience with triangular CarboFix "Piccolo" Distal Radius Plate in wrist fractures. Clinical and radiological results. - Guzzini, Matteo; Lupariello, Domenico; Lanzetti, Riccardo Maria; Mazza, Daniele; Ferretti, Andrea (Acta Biomedica Atenei Parmensis, 2018)
Background and aim o the workIn the recent last years there was a diffusion of new radiolucent plates for the treatment of distal radius fractures.The aim of our study is to evaluate the clinical and radiological outcomes at 12-month-follow-up for the treatment of distal radius fracture with the new triangular CarboFix "Piccolo" Distal Radius Plate.MethodsAll consecutive patients aged from 18 or over, who were treated for unstable distal radius fracture with a volar CarboFix "Piccolo" Distal Radius Plate with triangular design between September 2015 and May 2016, have been included in the study.From the original 28 patients, 6 patients were lost to the follow up or did not meet the inclusion criteria and 22 were available for the study.  The 22 patients were prospectively reviewed with dynamometric,radiographic and clinical evaluations (ROM, VAS, Quick DASH).ResultsThe mean follow-up was 15.7 months. All fractures healed, and radiographic union was observed at an average of 5 weeks. All patients have recovery of R.O.M. comparable to the contralateral at the final follow up; with no significant difference (p>0.05) as regards extension, flexion, ulnar deviation, radial deviation, supination and pronation comparing to the unaffected arm. At final follow-up, no patients had a statistically significant difference (p>0.05) of grip strength, comparing to the contralateral side. The mean Quick DASH was 9.3 and the mean VAS score was 2.3.ConclusionThe most important finding of the present study was that the triangular CarboFix "Piccolo" Distal Radius Plate showed good clinical and radiological results in the treatment of distal radial fractures. These results are comparable to those achieved with conventional plates.